2016
DOI: 10.1302/2058-5241.160028
|View full text |Cite
|
Sign up to set email alerts
|

Foot and ankle tendoscopies: current concepts review

Abstract: Tendoscopy is an apparently safe and reliable procedure to manage some foot and ankle disorders.The most common foot and ankle tendoscopies are: Achilles; peroneal; and posterior tibial tendon.Tendoscopy may be used as an adjacent procedure to other techniques.Caution is recommended to avoid neurovascular injuries.Predominantly level IV and V studies are found in the literature, with no level I studies still available.There are many promising and evolving endoscopic techniques for tendinopathies around the foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…25 A reparação endoscópica dos peroneais parece igualmente vir a ser uma opção válida 26 , embora a reparação aberta permaneça ainda como a técnica de eleição. 13,23,27, 28 A reabilitação dos doentes submetidos a sutura da rotura longitudinal dos peroneais segue protocolos com uma fase inicial de imobilização rígida (2 a 6 semanas) em descarga, seguindo-se um período de carga gradual e treino de força. Pode adotar-se um protocolo mais dinâmico com o recurso a uma bota tipo walker e a carga gradual precoce a partir das duas semanas.…”
Section: Discussionunclassified
“…25 A reparação endoscópica dos peroneais parece igualmente vir a ser uma opção válida 26 , embora a reparação aberta permaneça ainda como a técnica de eleição. 13,23,27, 28 A reabilitação dos doentes submetidos a sutura da rotura longitudinal dos peroneais segue protocolos com uma fase inicial de imobilização rígida (2 a 6 semanas) em descarga, seguindo-se um período de carga gradual e treino de força. Pode adotar-se um protocolo mais dinâmico com o recurso a uma bota tipo walker e a carga gradual precoce a partir das duas semanas.…”
Section: Discussionunclassified
“…Monteagudo et al (15) state that tendoscopy is an apparently safe and reliable procedure for treating some foot and ankle disorders, and it can be used as an adjuvant procedure to other techniques. Level IV and V studies are predominantly found in the literature, and level I studies are not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…retrotalar tunnel. [15][16][17][18][19] It not only addresses a local tendon problem but also restores the normal functional anatomy of the foot by drastically improving local and remote biomechanics. 5 The arthroscopically assisted section of the retrotalar pulley and the subsequent re-establishment of the tendon glide restore the subtalar mobility and allow the kinetic chain of the lower extremity to regain its natural dynamic balance, as we observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 Furthermore, this technique provides a good alternative to the already existing open surgical approaches for FHL release and represents the first technique described to address the issue of FHL conflict during its passage through the retrotalar tunnel. 15 , 16 , 17 , 18 , 19 It not only addresses a local tendon problem but also restores the normal functional anatomy of the foot by drastically improving local and remote biomechanics. 5…”
Section: Discussionmentioning
confidence: 99%